The Impact of the COVID-19 Pandemic on Self-Reported Health - Peters, Annette; Rospleszcz, Susanne; Greiser, Karin H; Dallavalle, Marco; Berger, Klaus (Deutsches Ärzteblatt international, 2020)
The pandemic caused by the coronavirus SARS-CoV-2 and the countermeasures taken to protect the public are having a substantial effect on the health of the population. In Germany, nationwide protective measures to halt the spread of the virus were implemented in mid-March for 6 weeks. In May, the impact of the pandemic was assessed in the German National Cohort (NAKO). A total of 113 928 men and women aged 20 to 74 years at the time of the baseline examination conducted 1 to 5 years earlier (53%) answered, within a 30-day period, a follow-up questionnaire on SARS-CoV-2 test status, COVID-19- associated symptoms, and self-perceived health status. The self-reported SARS-CoV-2 test frequency among the probands was 4.6%, and 344 participants (0.3%) reported a positive test result. Depressive and anxiety-related symptoms increased relative to baseline only in participants under 60 years of age, particularly in young women. The rate of moderate to severe depressive symptoms increased from 6.4% to 8.8%. Perceived stress increased in all age groups and both sexes, especially in the young. The scores for mental state and self-rated health worsened in participants tested for SARS-CoV-2 compared with those who were not tested. In 32% of the participants, however, self-rated health improved. The COVID-19 pandemic and the protective measures during the first wave had effects on mental health and on self-rated general health.